Analyses on local kyzilkum sand for water filter loading (Международный научный журнал «Инженер», 2026)
This article discusses the consequences of the depletion of drinking water, one of the urgent problems of today,and solutions to the problem, improving water quality through filtration, the productive use of local Kyzylkumsand as a method of reuse, the difference between Kyzylkum sand and other local raw materials, the effectivenessof water filtered through Kyzylkum sand (especially black sand), the issue of wastewater and technical waterpurification and recycling from this sand. An experiment was conducted based on Darcy's law and a device wasbuilt based on this law. The work being done in developed countries in this regard, their significance, and practicalapplication were discussed. The results of the analyzes and experiments conducted using the V1100spectrophotometer and TDS&EC testers are presented in the form of tables, figures, and diagrams.